Aportes de la meta teoría al método diplomático en Archivología - Tognoli, Natália Bolfarini [UNESP]; Guimarães, José Augusto Chaves [UNESP] (My University, 2013)
Since the late twentieth century Diplomatics occupies an important place in teaching and researching in Archival Science, once its method supports the main processes of record management. This paper discusses the relationship between both disciplines from the perspective of the diplomatic method based on Ritzer’s metatheoretical studies, synthesizing the three approaches of Diplomatics (Classical, Modern and Contemporary) in order to think about an ideal type of diplomatic analysis that effectively sustain its methodological support to archival practice.
Contribuições da metateoria para o método diplomático em Arquivologia
The contributions of metatheory to the diplomatic method in Archival science
Keywords: Archival science; Diplomatic method; Diplomatics; Metatheory